Decolonial research, languages and practices in/with education: Decolonial research, languages and practices in/with education - Ferreira da Silva, Gilberto; Aquino Machado, Juliana (Diálogos Latinoamericanos, 2024)
The present study, of an essayistic nature, discusses the relations between science, research, languages, and practices as an experience in and with education. Initially, it proposes a reflection about the crossings between a colonized life and a decolonial posture. In the second moment, it highlights a decolonial way of doing as a possibility, placing itself in dialogue with other knowledges, from where research postures emerge that are capable of leading the production of knowledge on other bases, distancing itself from the modern western hegemonic model. Finally, when thinking of other ways of researching and producing knowledge, the experimentation of new/other ways of writing and expressing experiences in education is concretized in an effort to search for coherence, which reveals the meaning between what is said, from where it is said, and what is done and with whom.